Infectiological Outcome of Total Hip and Total Knee Arthroplasty in Post-Traumatic and Primary Osteoarthritis - Maximilian Gresch; Nikolaus von Dercks; Nadine Dietze-Jergus; Andreas Roth; Christina Pempe (Antibiotics)
Background: The objective of this study was to compare infection rates, pathogen species detection and antimicrobial susceptibility testing in patients with total hip arthroplasty (THA) and total knee arthroplasty (TKA) following post-traumatic osteoarthritis (PTOA) and primary osteoarthritis (POA). Results: Patients undergoing both THA and TKA were significantly more likely to have a PJI after PTOA than after POA (THA: 2.5% vs. 10.2%, p = 0.003; TKA: 3.2% vs. 10.3%, p = 0.028). The most frequently detected pathogen in both THA and TKA was Staphylococcus spp. Among patients with a PJI in THA, Staphylococcus spp. was detected in 47% after POA and 60% after PTOA. Among patients with a PJI in TKA, Staphylococcus spp. was isolated in 59% after POA and 80% after PTOA. The remaining pathogens were mainly Enterococcus spp., Enterobacterales and anaerobic bacteria. After THA, beta-lactam-resistant staphylococcal isolates were detected more frequently in PTOA patients than in POA patients (13% vs. 100%, p = 0.024). There was no difference in the beta-lactam staphylococcal resistance rate in patients after TKA (20% vs. 25%, p = 0.945). Furthermore, an analysis of susceptibility testing from all groups showed that significantly more pathogens were susceptible to vancomycin than to cefuroxime (76% vs. 45%, p < 0.001) or clindamycin (76% vs. 52%, p = 0.007). Methods: A retrospective analysis was performed using clinic-owned data during the period January 2016–December 2020. A total of 1485 patients following primary implantation of THA or TKA due to PTOA or POA were included. Early-onset periprosthetic joint infection (PJI), defined according to the 2018 Definition of Periprosthetic Hip and Knee Infection Criteria, was evaluated. Conclusions: Therefore, the use of vancomycin as a perioperative prophylaxis should be discussed under benefit/risk consideration in further studies.